Natural Variation Reveals a Key Role for Rhamnogalacturonan I in Seed Outer Mucilage and Underlying Genes - Fabrissin, Isabelle (Plant Physiol, 2019)
On imbibition, Arabidopsis (Arabidopsis thaliana) seeds release polysaccharides from their epidermal cells that form a two-layered hydrogel, termed mucilage. Analysis of a publicly available data set of outer seed mucilage traits of over 300 accessions showed little natural variation in composition. This mucilage is almost exclusively made up of rhamnogalacturonan I (RGI), highlighting the importance of this pectin for outer mucilage function. In a genome-wide association study, observed variations in polymer amount and macromolecular characteristics were linked to several genome polymorphisms, indicating the complexity of their genetic regulation. Natural variants with high molar mass were associated with a gene encoding a putative glycosyltransferase called MUCILAGE-RELATED70 (MUCI70). muci70 insertion mutants produced many short RGI polymers that were highly substituted with xylan, confirming that polymorphism in this gene can affect RGI polymer size. A second gene encoding a putative copper amine oxidase of clade 1a (CuAOα1) was associated with natural variation in the amount of RGI present in the outer mucilage layer; cuaoα1 mutants validated its role in pectin production. As the mutant phenotype is unique, with RGI production only impaired for outer mucilage, this indicates that CuAOα1 contributes to a further mechanism controlling mucilage synthesis.